Efektivitas Implementasi Buku Ajar Matematika Berbasis Literasi dan Numerasi melalui Pembelajaran Project Based Learning (PBL) untuk Siswa Sekolah Menengah Atas - Ladyawati, Erlin; Rahayu , Sri (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
The purpose of this study was to describe the effectiveness of the implementation of literacy and numeracy-based mathematics textbooks through PBL learning for class XI high school students through Problem Based Learning (PBL). This research is still in the circle of previous research, namely the development of literacy and numeracy-based mathematics textbooks for high school which was developed with the ADDIE development model. This research is included in the implementation phase. This research uses a descriptive quantitative approach. The subjects of this study were students of class XI-A SMA Wachid Hasyim 2 Taman Sidoarjo with a total of 35 students. The technique used is a test technique to determine the improvement of literacy and numeracy skills and a test technique to determine learning independence and student responses. From the results of the data obtained in this study, the results for literacy and numeracy ability tests were analyzed using N-Gain scores resulting in the "High" category, students’ independence in learning mathematics through textbooks designed to produce a "Good" category, and student responses to learning and textbooks in the "Good" category. If you look at the results obtained, it can be concluded that the implementation of literacy and numeracy-based mathematics textbooks through Project Based Learning (PBL) for high school students is said to be effective.